Rik mans frilla eller fattig mans fru? - Magnúsdóttir, Auður (Kvinder, Køn & Forskning, 1997)
It is commonly accepted that marriage was an important political institution in the middle ages. Marriage was one way of making allies, confirming friendship between the two involved families, or even reconciliation. This was by no means different in the Icelandic freestate. Through marriage chieftains like Snorri Sturluson, and his brother ҂órdur, both secured and increased their influence. On the other hand, both Snorri and ҂órdur had concubines; Snorri most likely while he was still married but ҂órdur between his two marriages. In fact, concubinage was common in the Icelandic freestate and the attempts of the church to abolish the custom had little effect. Even though there were differences between legitimate marriage and concubinage my thesis is that both institutions were of great importance politically, perhaps even increasing in the struggle for power we witness in the last hundred years og the Icelandic freestate. The concubines were generally of lower social status than the men they had relations with, but frequently daughters of wealthy farmers with influence in their territories. Becoming a concubine was probably a result of negotiation between two families, as was the case with marriage, and though this connection the women’s father or/and brothers and the chieftain became allies.